Influenza vaccine effectiveness against influenza-associated hospitalization in 2015/16 season, Beijing, China. Issue 23 (25th May 2017) - Zhang, Yi; Wu, Peng; Feng, Luzhao; Yang, Peng; Pan, Yang; Feng, Shuo; Qin, Ying; Zheng, Jiandong; Puig-Barberà, Joan; Muscatello, David; MacIntyre, Raina; Cowling, Benjamin J.; et al.
Abstract: Background: Vaccination is recommended to prevent influenza virus infection and associated complications. This study aimed to estimate the influenza vaccine effectiveness (VE) against hospitalization in the 2015/16 season in Beijing. Methods: Patients who were hospitalized in the 5 study hospitals between 1 Oct 2015 and 15 May 2016 were recruited. Influenza vaccination status was obtained for PCR-confirmed influenza patients and the selected controls who tested negative for the virus. Conditional logistic regression was used to estimate the influenza VE matching by calendar week, and adjusting for age, study sites, underlying medical conditions, smoking status, and hospital admissions over the past 12 months. Results: The overall VE was −37.9% (95% CI: −103.3, 6.5) against laboratory-confirmed influenza-associated hospitalization. The 2015–16 seasonal vaccine was had −61.9% (95% CI: −211.9, 15.9), −5.4% (95% CI: −108.1, 46.6) and −45.2% (95% CI: −152.6, 16.5) effectiveness to prevent infection from A(H1N1)pdm09, A(H3N2) and influenza B, respectively. Conclusions: Influenza vaccination did not show effective protection against hospitalization with influenza in 2015/16 season in Beijing.